2016
DOI: 10.1017/s1751731116001002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the level of early productivity on the lifespan of ewes in contrasting flock environments

Abstract: Selection for high levels of prolificacy has allowed substantial improvements in the production efficiency of New Zealand (NZ) sheep farms, but the consequences on ewe lifetime performance are mostly unknown. In this study, the relationship between the level of prolificacy early in ewes' productive lives and their probability to survive later (i.e. stayability) was evaluated in two contrasting NZ flock environments. Records were obtained from 6605 ewes from four ram breeder flocks representing either a moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Using a bioeconomic model, Farrell reported that for a New Zealand North Island Hill Country sheep farm with 21% of the flock lost annually due to wastage, a reduction in wastage to 5% could increase cash profit by 33% [1]. Combined, this indicates that it is important for replacement hoggets to remain in a flock, and be productive, for a sufficient period to be economically efficient [6,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Using a bioeconomic model, Farrell reported that for a New Zealand North Island Hill Country sheep farm with 21% of the flock lost annually due to wastage, a reduction in wastage to 5% could increase cash profit by 33% [1]. Combined, this indicates that it is important for replacement hoggets to remain in a flock, and be productive, for a sufficient period to be economically efficient [6,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating ewe mortality rates and timing in extensive outdoor pastoral farming systems have largely focused on data collection at key production times (i.e., weaning, pre-mating, mid-pregnancy, and pre-lambing) with the estimation of mortality rates based on sheep missing at these times [8,[12][13][14]. A large New Zealand study identified that the majority of ewes that went missing and were presumed to have died, or were reported as dead, did so over the mid-pregnancy to weaning period, but the causes of death were not investigated [8].…”
Section: Introductionmentioning
confidence: 99%
“…Reproductive indicators measured earlier in life might be helpful in making a selection and culling decisions, given that they are, to some extent, associated with the ewes' total or lifetime reproductive performance. Authors of several studies used this presumption in an effort to explain or predict ewe reproductive performance (Lee and Atkins, 1996;Amer et al, 2007;Lee et al, 2014;Kleemann et al, 2016) or its stayability (Douhard et al, 2016).…”
Section: Discussionmentioning
confidence: 99%